Pengaruh Kompetensi Profesional, Kompetensi Pedagogik dan Motivasi Kerja Guru Terhadap Hasil Belajar Siswa - Zhafarina Maharani Idzni; Lantip Diat Prasojo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Teacher competence and teacher motivation in teaching greatly influence student learning outcomes. Looking at the average student learning outcomes (Regional Education Standards Assessment) in 2024, grade IX junior high school students in Sanden District, Bantul, DIY are very diverse. Not a few schools are able to maintain school quality by preparing their students to get maximum scores at the end of each semester. Especially grade IX junior high school students who face ASPD. Many of the students do not care about the ASPD results at the junior high school level because they think the junior high school level is not as important as the Final School Exam at the high school level later. The purpose of this study is to determine the professional competence of teachers, pedagogical competence and teacher motivation on the learning outcomes of junior high school students in Sanden District, Bantul Regency, DIY. This type of research is ex-post facto with a quantitative approach. The population of this study was 136 junior high school teachers in Sanden District, Bantul Regency, DIY. The determination of the research sample of 101 used the Slovin formula. The instrument validity test used the Pearson Product Moment correlation. The instrument reliability test used the Cronbach's Alpha coefficient. The results of this study indicate that the professional competence, pedagogical competence and work motivation of teachers in junior high schools in Sanden District, Bantul, DIY are in the good category.